Examining customer satisfaction and purchase intention toward a new product before its launch: Cookies enriched with spirulina - Istijanto; Yalun Arifin; Nurhayati (Cogent Business & Management, 2023)
This study aims to examine the effects of product attributes during the prototype stage on customer satisfaction and intention to buy. The new product examined was cookies enriched with spirulina. The theories serving as the foundation of explanation were Stimulus-Organism-Response (S-O-R) theory and Expectation Confirmation Theory (ECT). The current research employed a survey method. Using judgmental sampling, 316 respondents were given samples of a prototype product to experience the product realistically. The measuring items had a 7-point numerical rating scale. The data were collected and then analysed using Structural Equation Modelling with LISREL 8.7. The results showed that the cookies' aroma, taste, colour, shape, and perceived healthiness influenced customer satisfaction and intention to buy. However, two other attributes, the texture and thickness of the cookies, did not significantly influence customer satisfaction. The findings contribute to the knowledge of customer satisfaction with a new product and the literature on food product attributes. For practitioners, this study provides a valuable analytical technique for testing a new product comprehensively before its launch.
Keywords: 650; cookies; customer satisfaction; new product; prototype; purchase intention; spirulina